Production monétaire et stratégies d’approvisionnement de l’argent en Occident nord-méditerranéen (iie-ier siècle av. n. è.) - Charles Parisot-Sillon; Guillaume Sarah (Mélanges de la Casa de Velázquez)
Coining was one of the main and most widely-known uses of silver in the north of the western Mediterranean, and hence numismatic sources seem particularly appropriate to characterise the use to which precious metals were put in that region. The lack of coincidence between the principal silver-producing regions and coin-producing sites evidences the breadth and the originality of the routes of silver circulation between the Iberian Peninsula and Italy. The numismatic and archaeometric study of the most important western coinages identifies firstly the geography of these supply circuits, and secondly the economic strategies and modes of production followed at the mints. This article lays particular stress on the diversity of provenance of the metal used in Iberian mints and the successive phases in the supply to the mint at Rome over the last two centuries BCE.